2016
DOI: 10.1371/journal.pone.0156662
|View full text |Cite
|
Sign up to set email alerts
|

Association between Asthma and Autism Spectrum Disorder: A Meta-Analysis

Abstract: ObjectiveWe conducted a meta-analysis to summarize the evidence from epidemiological studies of the association between asthma and autism spectrum disorder (ASD).MethodsA literature search was conducted using PubMed, Embase, and Cochrane library for studies published before February 2nd, 2016. Observational studies investigating the association between asthma and ASD were included. A random effects model was used to calculate the pooled risk estimates for the outcome. Subgroup analysis was used to explore pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 31 publications
9
34
0
2
Order By: Relevance
“…the presence of more than 1 chronic physical condition) in people with mental illness. Nonetheless, some recent large scale multi-national studies have demonstrated that people with SMI 41,48 , CMDs 49,50 and SUDs 18,51 are at greatly increased risk of physical multimorbidity, right from illness onset. 52 Multimorbidity occurs from a relatively young age in people with mental illness 41,52 , and greatly increases personal and economic burden associated with chronic conditions, while also reducing life expectancy.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…the presence of more than 1 chronic physical condition) in people with mental illness. Nonetheless, some recent large scale multi-national studies have demonstrated that people with SMI 41,48 , CMDs 49,50 and SUDs 18,51 are at greatly increased risk of physical multimorbidity, right from illness onset. 52 Multimorbidity occurs from a relatively young age in people with mental illness 41,52 , and greatly increases personal and economic burden associated with chronic conditions, while also reducing life expectancy.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…16,17 Risk of asthma is also increased in autism. 18 In bulimia, there is a marked increase in risk of diabetes (OR 3.45) and in anorexia, the risk is significantly decreased (OR 0.71). 19 The risk of osteoporosis is increased over twelve-fold in the latter.…”
Section: Other Mental Disordersmentioning
confidence: 99%
“…ASD is a complex and heterogeneous disorder. Due to the social, cognitive, and behavioral limitations associated with ASD, individuals with ASD are found to be more likely to suffer from physical conditions such as obesity and gastrointestinal disorders [Bresnahan et al, ; Zheng et al, ], but not other medical conditions such as asthma and allergies [Lyall, Van de Water, Ashwood, & Hertz‐Picciotto, ; Zheng et al, ]. Furthermore, ASD is also often found to be comorbid with mental health disorders such as schizophrenia and attention deficit/hyperactivity disorder [Antshel, Zhang‐James, & Faraone, ; Panagiotidi, Overton, & Stafford, ].…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of ASD is 1 in 68 children 11 . Additionally, ASD is co-morbid with mental health disorders such as anxiety disorder and attention deficit/hyperactivity disorder but not with medical condition such as asthma and allergy 1215 . Since ASD is a serious public health problem, scientists have attempted to identify biomarkers to achieve an earlier diagnosis and enable earlier treatment.…”
Section: Introductionmentioning
confidence: 99%